How Activists Overcome Alienation through Learning and Collective Action: Considerations from a Recent Case Study - Joseph E. Sawan (Adult Education Research Conference, 2011)
This paper discusses how a recovery of Marx’s theory of alienation can prove fruitful in understanding social movement activity. As globalized capitalism continues to fragment human social relations, people are coming together to envision alternatives and reclaim their communities. How can we understand such activity in the context of alienation? I begin with an outline of Marx’s method and theory of alienation in the context of social movements, followed by preliminary findings from a recent case study with housing activists engaged in strategies for de-alienation through anti-poverty organizing and learning.
Keywords: alienation; social movements; popular education; anti-poverty organizing